1984
DOI: 10.1016/0014-5793(84)81000-5
|View full text |Cite
|
Sign up to set email alerts
|

Solubilized monomeric sarcoplasmic reticulum Ca pump protein

Abstract: Phosphorylation (by inorganic phosphate) of sarcoplasmic reticulum Ca pump protein has been studied in a detergent solution in which the protein has been previously shown to exist as a monomer. The course of the reaction is qualitatively similar to that observed for membrane-bound (possibly oligomeric) protein.In particular, the results indicate that alternation between the two principal conformational states of the Ca pump protein persists in the monomeric state, which suggests that the machinery for coupling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…It was necessary to assume that binding of Mg2+ to these sites was not affected by pH, since otherwise binding constants that give inhibition at pH 6.2 gave too large inhibitions at pH 8.0. Even so, it was impossible to simulate the large decrease in phosphorylation levels reported to occur at the highest concentrations of Mg2+ (Loomis et al, 1982;Martin & Tanford, 1984) without obtaining inhibitions inconsistent with the data of Punzengruber et al Inesi et al (1984). However, since Loomis et al (1982) found that up to 40% of the binding of [32P]phosphate was non-specific at high Mg2+ concentrations, we believe the simulations to be acceptable.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…It was necessary to assume that binding of Mg2+ to these sites was not affected by pH, since otherwise binding constants that give inhibition at pH 6.2 gave too large inhibitions at pH 8.0. Even so, it was impossible to simulate the large decrease in phosphorylation levels reported to occur at the highest concentrations of Mg2+ (Loomis et al, 1982;Martin & Tanford, 1984) without obtaining inhibitions inconsistent with the data of Punzengruber et al Inesi et al (1984). However, since Loomis et al (1982) found that up to 40% of the binding of [32P]phosphate was non-specific at high Mg2+ concentrations, we believe the simulations to be acceptable.…”
Section: Discussionmentioning
confidence: 84%
“…2 and 3), at high Mg2+ concentrations these levels fall. This has been attributed to the binding of Mg2+ to the Ca2+-binding sites of the El conformation of the ATPase (Loomis et al, 1982;Martin & Tanford, 1984). Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…On the other hand, structural studies suggest that the Ca2+-ATPase peptides may form dimeric or higher oligomeric complexes in the membrane, which could be the minimal transport units (5)(6)(7). In favor of the view that the functional unit in Ca2+ transport is a monomeric peptide (8) are findings that show that it is possible to prepare soluble monomeric Ca2+-ATPase in detergent with retention of important functional properties, such as ATP hydrolysis (3) accompanied by release of Ca2+ from the two high-affinity transport sites (9,10) and ability to catalyze resynthesis of ATP from ADP and Pi after a "jump" in Ca2+ concentration (10)(11)(12). However, based on kinetic evidence obtained with soluble preparations of oligomeric and monomeric Ca2+-ATPase, it has been argued that peptide-peptide interactions are required for coupling between the ATPase reaction and Ca2+ translocation (13)(14)(15).…”
mentioning
confidence: 98%